Effect of Traditional Curd Supplementation and Probiotics on Growth Performance and Frequency of Diarrohea in Cattle Calves Under Farmer's field - Khadda, Balbir Singh; Kanak Lata,; Raj Kumar,; Khajuria, S.; Aashaq Hussain Dar, (Indian Journal of Animal Nutrition, 2021)
A trial was conducted to evaluate the effect of supplementary feeding of curd as probiotics on growth performance and frequency of diarrohea in pre- ruminant cattle calves under farmerâ€™s field in semi- arid condition of central Gujarat, India. Twenty four, pre-ruminant female Gir cattle calves with average age of fifteen days were selected randomly and distributed equally in to four groups, six each in a completely randomized design i.e. T1- basal diet (control), T2 - basal diet + Saccharomyces cerevisiae @ 5 g per calf/ day, T3 - basal diet + Lactobacillus acidophilus @ 1 g (2 x 1010 cfu/ g) per calf/ day and T4 - basal diet + Traditional curd @ 50 mlÂ  per calf/ day, respectively for a period of 90 days. The results of the study revealed that the average daily gains and final body weight of calves was significantly (P